Personality Traits as Predictors of Burnout and Work-Life Balance in Healthcare Practitioners - Kashyap, Himani; Ahmad, Ambrien (Journal of Neonatal Surgery, 2025)
Healthcare professionals face immense psychological and emotional challenges due to the demanding nature of their work. Burnout and work-life balance are pressing concerns that significantly impact their well-being and job performance. This review explores the role of personality traits in predicting burnout and work-life balance, drawing on empirical studies and theoretical perspectives such as the Job Demands-Resources (JD-R) model. The findings indicate that neuroticism is a significant risk factor for burnout, while conscientiousness, extraversion, and agreeableness act as protective factors. The review also highlights gaps in the literature, including the need for longitudinal studies, cross-cultural research, and intervention-based approaches tailored to individual personality profiles. Addressing these gaps can help develop targeted strategies to enhance resilience and well-being among healthcare professionals.